EFFECTS OF LANDUSE AND LANDCOVER CHANGE ON FLOODING IN KANO METROPOLIS, KANO STATE, NIGERIA - Mukhtar, I.; Iguisi, E. O.; Shehu, A. U.; Dabo, Yusuf; Abubakar, M.; Zubairu, S. M.; Balarabe, A. (FUDMA JOURNAL OF SCIENCES, 2020)
ABSTRACTThis paper looked at the change in land use land cover (LULC) of Kano metropolis from 2001 to 2012; projected to 2035 and thereby assessing the response of these different land covers to rainfall event using the Hydrologic Engineering Corps- Hydrologic Modelling System (HEC-HMS) model. The outcome of the LULC revealed that the built-up areas increased from 19.7% to 34.4% and then to 54.4% in 2001, 2012 and 2035, respectively. The discharge of Jakara basin indicated a rise from 2001, 2012 to 2035 in the order of 443, 585.2 to 609.7 cm3/sec respectively. However, that of Chalawa shows increase between 2001 and 2012 and a decrease in 2035 as a result of canalization within the basin. The paper recommended adherence to the city masterplan and construction of canals within each sub-drainage basin for proper conveyance of run-off discharge.
Keywords: Landuse and Landcover (LULC), HEC-HMS model, Chalawa basin, Jakara basin and sub- drainage basins